1999
DOI: 10.2307/3285776
|View full text |Cite
|
Sign up to set email alerts
|

Cold Stress-Induced Modulation of Cell Immunity during Acute Toxoplasma gondii Infection in Mice

Abstract: Infection with Toxoplasma gondii in the acute phase results in nonspecific suppression of immunologic function in mice and humans. The present study examined the effects of a physical stressor, i.e., cold stress (CS), on macrophage function (nitrite production, parasite survival) and splenic blastogenesis in the acute phase of murine T. gondii infection. In our stress paradigm, female BALB/c mice were placed in cold water (1 +/- 0.5 C), 5 min each day for 8 days. Nitrite production and parasite survival were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 29 publications
3
41
2
Order By: Relevance
“…This work extends our previous studies on the immunomodulatory effects of CS during T. gondii infection [36,37]. We have shown that macrophages from CS mice produced lower levels of nitric oxide, and had a decreased ability to kill T. gondii compared to infected control mice.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…This work extends our previous studies on the immunomodulatory effects of CS during T. gondii infection [36,37]. We have shown that macrophages from CS mice produced lower levels of nitric oxide, and had a decreased ability to kill T. gondii compared to infected control mice.…”
supporting
confidence: 75%
“…Cell proliferation was enhanced in CS mice but depressed in the infected group during the 1st week after infection. This effect was reversed during the 2nd week, cell proliferation was enhanced in infected mice, but depressed in CS animals [36]. In addition, CS appeared to have a protective role in mice orally infected with cysts of the ME49 strain of T. gondii [37].…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Several authors showed that cold stress profoundly modulated immune response and the outcome of infections because many mediators released during physical stress, such as glucocorticoids and catecholamines, influenced the growth and multiplication of pathogens, including T. gondii [711,[721][722][723][724]. Cold stress can suppress [725,726] or enhance [727,728] immunity by inducing and/or enhancing the synthesis of specific proteins with relevant roles in transcription, translation, and recombination [729,730].…”
Section: Hypothermia and T Gondii Infectionmentioning
confidence: 99%